Design of binary and ternary nitrate salt mixtures for energy storage and heat transfer in solar thermal systems - Upadhyay, Abhishek (My University, 2016)
The objective of the present study is to obtain molten salt having higher thermal stability, reduced cost and relatively lower melting point as compared to previously available molten salts. A very large range of molten blends of alkali nitrates are inspected by experimental approach. Since the determination of eutectic concentration, melting point and phase diagram from experimental methods are usually costly and time consuming; therefore it is of interest to predict the same by using some numerical method. In this work, the numerical method based on regular solution theory is used to predict eutectic concentration and melting point of the binary and ternary systems consisting of NaNO3, KNO3 and LiNO3 salts. The melting points of binary and ternary systems are also determined experimentally using Differential Scanning Calorimeter (DSC) and then they are compared with those predicted by the numerical method. Thermo-Gravimetric analysis (TGA) is also used to determine thermal stability of three binary and a ternary mixtures at various temperature. The experimental values obtained from instruments are found to be in good agreement with the predicted values obtained from numerical method. The experimental results show that the ternary salt studied in this work has a melting point of 121°C. This salt mixture is thermally stable up to temperature of 534°C and can be used up to a temperature of 608°C for a short period of time. This ternary salt mixture is also cost effective due to lower concentration of lithium nitrate in the salt mixture.
Master of Engineering-Thermal Engineering
Keywords: Nitrate salt mixtures; eutectic composition; regular solution theory; solar energy; phase diagram